Personality, neuroticism, and coping towards the end of life - Chochinov, H.; Kristjanson, Linda; Hack, T.; Hassard, T.; McClement, S. (Elsevier, 2006)
The influence of personality characteristics on how patients cope with various challenges at the end of life has not been extensively studied. In order to exmine the association between end-of-life experience and neuroticism (defined within the personality literature as a trait tendency to experience psychological distress), a measure of neuroticism was administered to a cohort of dying cancer patients. Various other measure of physical, psychological, and existential distress were also measured to explore their possible connection to patient personality style. The personality characteristic neuroticism demonstrated a significant relationship with several end-of-life sources of distress, including depression, anxiety, sense of dignity, quality of life (rating and satisfaction), hopelessness, concentration, and outlook on the future. Neuroticism appears to have a significant association with the dying experience. This association is expressed across the psychological, existential and, to a lesser extent, physical and social domains of end-of-life distress. This may help clinicians identify vulnerable individuals who are most likely to have poorer adjustments and may benefit from earlier targeted interventional approches. Exploring the relationship between various facets of personality and end-of-life distress, and mapping this information against optimal therapeutic responses, remains the challenge for future research broaching this intriguing and largely ignored area of palliative care.